(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical characteristics of the TMJ images of patients with temporomandibular disorders at the Hospital of Can Tho University of Medicine and Pharmacy in 2021 - 2022. Methods: Patients with temporomandibular disorders were diagnosed according to McNeil (1997) criteria. The patient has one of three symptoms: Pain in the masticatory system, temporomandibular joint, and/or perianal region, often aggravated by palpation or functional activity. Jaw deviation when opening mouth with or without joint crackling. Limited mouth opening (≤ 40 mm). Agree to participate in the study. Sampling method: Convenience sampling over 35 patients. Results: Temporomandibular dysfunction appeared more in the age group from 16 to 35 (mean 28.54 ± 9.08). Women are more likely to get the disease than men, with a female/male ratio of 4/ first. Temporomandibular disorders appear in many students, students, and intellectual workers due to the impact of psychological stress factors. Clinical signs according to McNeil criteria: Pain in the joint area when moving the jaw accounts for 100%, and Arthralgia accounted for 82.5%. Limited opening of the mouth accounted for 48.6%. Status of TDH joints on Cone Beam Computed Tomography (CBCT) film: Round shape is the majority, with a rate of 59.4%. The flat shape has 3/35 patients (6.8%). The average size of the condyle in the T - S direction is 8.14mm; N - T dimension is 18.27mm. The condyle position posteriorly accounted for the majority (65.7%). Conclusion: The temporomandibular joint disorder seems to be significantly associated with depression, anxiety and stress, and the distribution of condylar position in the articular fossa has a different ratio between of the condyles in the study are round.